Wage growth and job mobility in the UK and Germany - Christian Dustmann; Sonia C. Pereira (Institute for the Study of Labor (IZA), 2005)
This paper investigates job mobility and estimates the returns to tenure and experience in the United Kingdom and Germany. We show evidence that job mobility is higher in the UK than in Germany, and that job movers may be negatively selected in Germany, but not in the UK. Our findings suggest that returns to experience are substantially higher in the UK. According to our estimates, ten years of labour market experience are associated with average wage returns of around 70 percent in the UK and 30 percent in Germany. Separate estimates for different qualification groups show that in Germany, it is the group of workers with apprenticeship training that is driving the low returns to labour market experience, while wages growth due to labour market experience is similar between the two countries for the other skill groups. Furthermore, returns to tenure are close to zero in both countries, while wage growth due to the macro trend is markedly higher in Germany.
Keywords: J24; J31; 330; returns to seniority; job mobility; asymmetric information